From Blackboard to Bot: The Evolution of English Language Teaching with Artificial Intelligence - Zahro, Wardatus; Ekowijayanto, Mochlis; Islam, Syaiful; Adi Pranata, Moh Sofyan (Corolla International Conference, 2025)
This study shows that the development of technology and the use of Artificial Intelligence (AI) specifically have a positive impact on students. Teachers also have a big challenge because teachers are motivators and must understand more about artificial Intelligence (AI). The researcher used a descriptive qualitative method to complete this research. Researchers collect data using observations, questionnaires and interviews. The questionnaire consisted of 10 questions. Artificial Intelligence (AI) is very useful for improving students’ writing skills in journal writing, where students can search and correct writing errors in artificial intelligence (AI). In conclusion, although artificial intelligence (AI) technology continues to develop rapidly and brings significant changes in the world of education, the role of teachers in instilling character remains irreplaceable. The aim of this research is to find out students’ perceptions of Artificial Intelligence (AI) and to determine the role of teachers in the era of Artificial Intelligence (AI). The contribution of this research is to enrich the literature on understanding the role of teachers in the context of learning using AI, developing an understanding of the transformation of the teacher’s role from a traditional teacher to a facilitator for students to learn based on AI. The contribution of this research is to enrich the literature on understanding the role of teachers in the context of learning using AI, developing an understanding of the transformation of the teacher’s role from a traditional teacher to a facilitator for students to learn based on AI.